Application of Capital Asset Pricing Model (CAPM) Sector Company Insurance - Andi Ratna Sari Dewi; Nurdjanah Hamid (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Application of Capital Asset Pricing Model in Insurance Sector Companies